2005
DOI: 10.1002/mawe.200500960
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of metals: modulation of intracellular calcium homeostasis

Abstract: Metals and metalloids with their organic derivatives are part of the environment occurring naturally or being introduced upon human activity (e.g. industry, agriculture or medicine). Even if they are useful for humans, these chemicals could be highly toxic (e.g. mercury, lead, arsenic, tin) acting as neurotoxins or carcinogens. Several human cases of metal derived intoxication have been documented resulting in health complications or ending with death. The mechanisms of toxicity are not well understood. Since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It has been demonstrated that intracellular calcium ([Ca 2+ ] i ) signals are involved in a number of events, including apoptotic pathways ( Mandic et al ., 2002 ; Arany et al ., 2004 ; Jaffe, 2005 ). While Ca 2+ could be released from the [Ca 2+ ] i stores, as it has been demonstrated for other metal compounds, such as trimethyltin or As 2 O 3 ( Florea and Büsselberg, 2005 , 2006 ; Florea et al ., 2005a , 2005b , 2007 ), Ca 2+ also could enter from the extracellular space through membrane channels. Recently it has been shown that the activation of inositol‐1,4,5‐trisphosphate (IP 3 ) receptors, found at the cellular membrane, results in an elevation of [Ca 2+ ] i ( Dellis et al ., 2006 ).…”
Section: Introductionmentioning
confidence: 73%
“…It has been demonstrated that intracellular calcium ([Ca 2+ ] i ) signals are involved in a number of events, including apoptotic pathways ( Mandic et al ., 2002 ; Arany et al ., 2004 ; Jaffe, 2005 ). While Ca 2+ could be released from the [Ca 2+ ] i stores, as it has been demonstrated for other metal compounds, such as trimethyltin or As 2 O 3 ( Florea and Büsselberg, 2005 , 2006 ; Florea et al ., 2005a , 2005b , 2007 ), Ca 2+ also could enter from the extracellular space through membrane channels. Recently it has been shown that the activation of inositol‐1,4,5‐trisphosphate (IP 3 ) receptors, found at the cellular membrane, results in an elevation of [Ca 2+ ] i ( Dellis et al ., 2006 ).…”
Section: Introductionmentioning
confidence: 73%
“…The imbalance of intracellular calcium homeostasis commonly leads to cellular apoptosis (Florea and Büsselberg, 2005). Accumulating data has reported that ROS can lead to the overload of Ca 2+ concentration in cells (Soliman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Mercury toxicity is also associated with an increase in intracellular Ca 2+ due to both an increase in the influx of Ca 2+ from the extracellular environment and an increase in the mobilization of intracellular reserves [ 60 ]. This effect on calcium homeostasis, associated with the effect of calcium increase due to OS, is responsible for the activation of proteases, lipases, and endonucleases.…”
Section: Mercury Exposure and Toxicitymentioning
confidence: 99%